Efektivitas Leader Member Exchange (LMX) dan Karakteristik Pekerjaan terhadap Organizational Citizenship Behavior (OCB) dengan Moderasi Person Organization Fit (Po Fit) - Sri Retno Hendrawati; Endang Tjahjaningsih (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2019)
This study aims to examine the influence of Leader Member Exchange (LMX) and job characteristics on Organizational Citizenship Behavior with the moderation of Person Organization Fit in Kardinah Hospital, Tegal City. The population of this study was civil servants with a minimum of high school education in Kardinah Hospital in Tegal City with a sample of 100 people. The sampling technique is stratified random sampling. The method of collecting data uses a questionnaire filled out by respondents. Testing instruments with validity and reliability tests. The analytical tool used is multiple regression, while to test the hypothesis using the t test. The results of the study show that leader member exchange has a positive and significant effect on organizational citizenship behavior. Job characteristics have a positive and significant effect on organizational citizenship behavior. The person organization fit moderates the relationship between leader member exchange towards organizational citizenship behavior. The person organization fit moderates the influence of job characteristics on organizational citizenship behavior.